If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -27 = 2c + -7 + -6e Reorder the terms: -27 = -7 + 2c + -6e Solving -27 = -7 + 2c + -6e Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. -27 + -2c = -7 + 2c + -2c + -6e Combine like terms: 2c + -2c = 0 -27 + -2c = -7 + 0 + -6e -27 + -2c = -7 + -6e Add '27' to each side of the equation. -27 + 27 + -2c = -7 + 27 + -6e Combine like terms: -27 + 27 = 0 0 + -2c = -7 + 27 + -6e -2c = -7 + 27 + -6e Combine like terms: -7 + 27 = 20 -2c = 20 + -6e Divide each side by '-2'. c = -10 + 3e Simplifying c = -10 + 3e
| 3Z+5=23 | | m^2+12m=-32 | | 2x+3=4(2x) | | 5/8x-3.5=7.66 | | (x-3-i)(x-3+i)=0 | | 0.035x+5.112=0.010x+5.107 | | 6+x+10=48 | | 3Z+15=21 | | b^2+b=30 | | 4(y-1)/5=2y+3 | | log[2](3x-5)=1 | | 5(a-4)(a+4)=0 | | 95y-21=y-64 | | 5y+3xy-7=0 | | n^2=-8n | | 6x/x-3+5x/x-4 | | 95(y-21)=64-y | | 10n^2+6=0 | | r^2=8-7r | | 4(2y+4)-6y=18 | | 2x^2-100=0 | | 28z-638=56 | | y^2+9y-36=0 | | 1/3x-9=10 | | 3r^2+11r=-12 | | -7+8(-2)=-23 | | (x^1/2)-(5x^1/4)+6=0 | | (1/3)y-5=7y+10-5y | | 29z-638=z+56 | | 3+x-4=17 | | 6b^2+11=-10b | | 8-(1-y)=7 |